Progress and challenges of carbon nanotube membrane in water treatment. Issue 11 (17th June 2016) - Lee, Jieun; Jeong, Sanghyun; Liu, Zongwen
ABSTRACT: The potential of the carbon nanotube (CNT) membrane has been highly strengthened in water treatment during the last decade. According to works published up to now, the unique and excellent characteristics of CNT outperformed conventional polymer membranes. Such achievements of CNT membranes are greatly dependent on their fabrication methods. Further, the intrinsic properties of CNT could be a critical factor of applicability to membrane processes. This article provides an explicit and systematic review of the progress of CNT membranes addressing the current epidemic—whether (i) the CNT membranes could tackle current challenges in the pressure- or thermally driven membrane processes and (ii) CNT hybrid nanocomposite as a new generation of materials could complement current CNT-enhanced membrane.